A Human MSH6 Germline Variant Associated With Systemic Lupus Erythematosus Induces Lupus‐like Disease in Mice. Issue 9 (16th June 2022) - Meas, Rithy; Nititham, Joanne; Taylor, Kimberly E.; Maher, Stephen; Clairmont, Kaylyn; Carufe, Kelly E. W.; Kashgarian, Michael; Nottoli, Timothy; Cheong, Ana; Nagel, Zachary D.; Gaffney, Patrick M.; Criswell, Lindsey A.; et al.
Abstract : Objective: To determine if single‐nucleotide polymorphisms (SNPs) in DNA repair genes are enriched in individuals with systemic lupus erythematosus (SLE) and if they are sufficient to confer a disease phenotype in a mouse model. Methods: Human exome chip data of 2499 patients with SLE and 1230 healthy controls were analyzed to determine if variants in 10 different mismatch repair genes ( MSH4, EXO1, MSH2, MSH6, MLH1, MSH3, POLH, PMS2, ML3, and APEX2 ) were enriched in individuals with SLE. A mouse model of the MSH6 SNP, which was found to be enriched in individuals with SLE, was created using CRISPR/Cas9 gene targeting. Wildtype mice and mice heterozygous and homozygous for the MSH6 variant were then monitored for 2 years for the development of autoimmune phenotypes, including the presence of high levels of antinuclear antibodies (ANA). Additionally, somatic hypermutation frequencies and spectra of the intronic region downstream of the VH J558‐rearranged JH4 immunoglobulin gene was characterized from Peyer's patches. Results: Based on the human exome chip data, the MSH6 variant (rs63750897, p.Ser503Cys) is enriched among patients with SLE versus controls after we corrected for ancestry (odds ratio = 8.39, P = 0.0398). Mice homozygous for the MSH6 variant ( Msh6 S502C/S502C ) harbor significantly increased levels of ANA. Additionally, the Msh6 S502C/S502C mice display a significant increase in the infiltration of CD68+ cells (a marker for monocytes and macrophages) into the lung alveolar space as well as apoptotic cells. Furthermore, characterization of somatic hypermutation in these mice reveals an increase in the DNA polymerase η mutational signature. Conclusion: An MSH6 mutation that is enriched in humans diagnosed with lupus was identified. Mice harboring this Msh6 mutation develop increased autoantibodies and an inflammatory lung disease. These results suggest that the human MSH6 variant is linked to the development of SLE.